Response of African oil palm to nitrogen addition and its influence on the diazotrophic bacteria population - Carvalho, André Vieira de; Alves, Bruno José Rodrigues; Reis, Veronica Massena (Pesquisa Agropecuaria Brasileira, 2006)
African oil palm (Elaeis guineensis, Jaquim) can produce up to 7 tons of oil per hectare per year. The vegetable oil is greatly versatile in its use, since food industry up to the production of fuels favorable to environmental protection. The plant has the potential to be associative with diazotrophic bacteria which colonize the roots and stem. The objective of this work was to evaluate 17 genotypes of E. guineensis in response to nitrogen addition and to verify the influence of this nitrogen on the diazotrophic population in an experiment using plastic pots filled with 50% quartz sand and 50% of non sterilized Horizon B; Red-Yellow Podzolic Soil series Itaguaí, extremely poor in nitrogen. Urea was used at a dose of 33.68 kg ha-1 de N. In the presence of the nitrogen, all genotypes improved biometric parameters, increased total nitrogen and its accumulation. Its addiction did not affect the diazotrophic population. Two genotypes were selected in the presence and absence of nitrogen: C-2001 and La Mé, respectively.